2016
DOI: 10.1039/c5ay02716k
|View full text |Cite
|
Sign up to set email alerts
|

Non enzymatic colorimetric detection of glucose using cyanophenyl boronic acid included β-cyclodextrin stabilized gold nanoparticles

Abstract: Gold nanoparticles generated and stabilized by a β-cyclodextrin–cyano phenyl boronic acid complex enable the colorimetric detection of glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Nevertheless, the sensitive enzymatic glucose sensors are associated with several drawbacks such as instability (pH, temperature and humidity) due to the denaturation of the enzyme, oxygen limitations and complex immobilization procedures [ 12 ]. Owing to the fast growth of the world population, ~422 million people in 2020 suffered from diabetes, and the number is expected to reach 592 million by 2035 [ 13 ]. Therefore, the development of an accurate, sensitive and low-cost electrochemical glucose sensor is of great need.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the sensitive enzymatic glucose sensors are associated with several drawbacks such as instability (pH, temperature and humidity) due to the denaturation of the enzyme, oxygen limitations and complex immobilization procedures [ 12 ]. Owing to the fast growth of the world population, ~422 million people in 2020 suffered from diabetes, and the number is expected to reach 592 million by 2035 [ 13 ]. Therefore, the development of an accurate, sensitive and low-cost electrochemical glucose sensor is of great need.…”
Section: Introductionmentioning
confidence: 99%
“…The use of in-situ synthesis of nanomaterials for colorimetric sensing has gained much attention due to its simplicity, ease of operation, and good sensitivity [ 21 ]. Some optical, colorimetric glucose sensing mechanisms based on noble metal nanoparticles have been presented in the literature, but most rely on pre-functionalization of particles or complementary use of enzymes or other catalytic reactions for the production of color signals, instead of using direct reactions between glucose and the precursor reagents, and there is yet to be such approach translated into a paper-based platform [ 22 , 23 , 24 , 25 , 26 , 27 ]. Nanostructured gold has also been applied in electrochemical sensing as a means of improving sensors catalytic capabilities, both in conjugation with GOx or for the development of non-enzymatic sensors [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies employing nanomaterials, such as nAg, nAu, carbon dots, carbon nanotubes, and quantum dots, have been reported for detection of biomarkers in the diagnosis and monitoring of diseases using cost-effective methodologies. In this context, a nonenzymatic colorimetric detection of glucose based on the inclusion of 4-cyanophenyl boronic acid (CPBA) with β-cyclodextrin stabilized nAu was developed for potential use in the management of diabetes . Results showed that the engineered nanoprobes possessed good solubility and exhibited good selectivity for glucose in aqueous media .…”
Section: Engineering Biomedical Devices For Potential Applicationsmentioning
confidence: 99%
“…In this context, a nonenzymatic colorimetric detection of glucose based on the inclusion of 4-cyanophenyl boronic acid (CPBA) with β-cyclodextrin stabilized nAu was developed for potential use in the management of diabetes . Results showed that the engineered nanoprobes possessed good solubility and exhibited good selectivity for glucose in aqueous media . Furthermore, the applicability of this method was validated using human blood serum samples which demonstrated that the developed methodology could detect glucose in the concentration range between 1–20 mM and hence can be exploited for detection of glucose in biological fluids .…”
Section: Engineering Biomedical Devices For Potential Applicationsmentioning
confidence: 99%